Using Information Systems And Intelligent Agents During Natural Occurrences (International Journal of Environmental Sciences, 2025)
Natural occurrences are often unpredictable, especially in a country like India, which has a large population, low literacy levels, and inadequate infrastructure. These factors can significantly amplify the impact of natural disasters. When such events occur, all living beings are affected. Although some disturbances can be predicted to a certain extent, the consequences remain severe due to the reasons mentioned above. To address this issue, this paper focuses on how mitigation efforts can be supported through the use of information systems. India is rapidly advancing in technology, and with the help of such systems, we aim to minimize the impact of natural disasters. However, building such systems is not as straightforward as developing other types of information processes. The proposed framework is designed to help people manage the effects of disasters and reduce their impact.